2019
DOI: 10.1186/s13287-019-1256-3
|View full text |Cite
|
Sign up to set email alerts
|

Inositol pyrophosphates mediated the apoptosis induced by hypoxic injury in bone marrow-derived mesenchymal stem cells by autophagy

Abstract: Objective: To investigate the potential effect of IP7 on the autophagy and apoptosis of bone marrow mesenchymal stem cells (BM-MSCs) caused by hypoxia. Methods: BM-MSCs isolated from adult male C57BL/6 mice were exposed to normoxic condition and hypoxic stress for 6 h, 12 h, and 24 h, respectively. Then, flow cytometry detected the characteristics of BM-MSCs. Furthermore, N6-(p-nitrobenzyl) purine (TNP) was administrated to inhibit inositol pyrophosphates (IP7). TUNEL assay determined the apoptosis in BM-MSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 46 publications
5
17
0
Order By: Relevance
“…Therefore, H/SD in vitro cellular model was performed to mimic the in vivo ischemic environment (34) . Concurrently, our results revealed that H/SD injury reduced cells survival and caused paracrine dysfunction of BM-MSCs (12) . Thus, promoting the low viability of BM-MSCs under hypoxic conditions after transplantation is crucial for elevating the e ciency of cellular therapy.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Therefore, H/SD in vitro cellular model was performed to mimic the in vivo ischemic environment (34) . Concurrently, our results revealed that H/SD injury reduced cells survival and caused paracrine dysfunction of BM-MSCs (12) . Thus, promoting the low viability of BM-MSCs under hypoxic conditions after transplantation is crucial for elevating the e ciency of cellular therapy.…”
Section: Discussionsupporting
confidence: 67%
“…Isolation, culture and treatments of BM-MSCs BM-MSCs were isolated and expanded as described (12) . Brie y, bone marrow was ushed from the femoral and tibia of adult Tg ( uc -egfp) mice with fetal bovine serum (FBS)-free Dulbecco's modi ed Eagle's medium (DMEM).…”
Section: Animalmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed platelet aggregation in Ip6k1-KO mice [183] is beneficial in thromboembolism, but may delay clotting in normal subjects. IP6K1 inhibits Akt in metabolic cells and tissues [12,29,40,[42][43][44][45]238]. In young, chow-fed tissues, IP6K1-disruption minimally alters Akt [22,29], whereas its perturbation reduces high fat diet or age induced Akt inhibition.…”
Section: Potential Risks Of Targeting the Ip6k Pathway In Metabolic Dmentioning
confidence: 99%
“…Isolation, culture and treatments of BM-MSCs BM-MSCs were isolated and expanded as described (10) . Briefly, bone marrow was flushed from the femoral and tibia of adult Tg(fluc -egfp) mice with fetal bovine serum (FBS)-free Dulbecco's modified Eagle's medium (DMEM).…”
Section: Introductionmentioning
confidence: 99%